Availability and Implementation of Instructional Materials in Science Teaching: A Glimpse of Gorkha District (Shanti Journal, 2022)
This paper focuses on the availability and implementation of instructional materials in science teaching with the main objectives to find the extent of laboratory and improvised materials used at the secondary level and to assess the practical activities completed by secondary science teachers prescribed in the science curriculum at the secondary level. This study is carried out based on the concept learning of Brunner, the cognition theory of Piaget and Skinner’s operant conditioning learning theory. This study is based on the descriptive survey design to explore the knowledge of teachers and students. For the study, eight public secondary schools within the Gorkha Municipality of Gorkha district were selected purposively and then eight science teachers were selected purposively and forty students selecting five students from each secondary level were selected using a simple random sampling method. A checklist, questionnaire and class observation guidelines were prepared and used to generate data. Data obtained from different tools were analyzed first using simple statistical methods quantitatively, then information obtained from class observation, the interview was analyzed qualitatively making themes and then interpreted linking with prescribed theory. From the data, it was found that most of the schools haven’t sufficient materials in their laboratory. Similarly, most of the science teachers have knowledge but they did not give priority to the improvised materials and did not follow the practical work prescribed in the science curriculum. Teachers can make materials; however, they were found depending upon the marketed science materials neglecting socio-culturally generated materials.